Immune-related alopecia (areata and universalis-type) in cancer patients receiving immune checkpoint inhibitors - Zarbo, A. (Br J Dermatol, 2017)
CTLA-4, PD-1, and PD-L1 monoclonal antibodies, commonly known as immune checkpoint inhibitors, are used for the treatment of various malignancies. The mechanism of action involves the inhibition of negative regulators of immune activation, which results in many patients developing immune-related adverse events (irAEs) including endocrinopathies, pneumonitis, colitis, hepatitis and dermatologic events. Dermatologic irAEs include maculopapular rash, pruritus, vitiligo, blistering disorders, mucocutaneous lichenoid eruptions, rosacea, and exacerbation of psoriasis. Alopecia secondary to immune checkpoint inhibitors has been reported in 1.0-1.6% of patients. We characterize four cases of alopecia areata (AA) secondary to immune checkpoint inhibitors with images, histology, and concomitant nail findings, including the first report of anti-PD-L1 therapy induced AA, and a review of the literature. Patients treated with immune checkpoint inhibitors, singly or in combination, who developed partial or complete alopecia (areata and universalis-type) during treatment for their underlying cancer were analyzed (N=4). Three (75%) patients had AA, while one (25%) had universalis-type. Two patients had resolution after topical, oral, or intralesional therapies and one patient had resolution after discontinuation of immunotherapy; all regrown hair exhibited poliosis. One (25%) patient had coincident onychodystrophy. This report describes a series of four patients who developed partial or complete alopecia (i.e. areata and universalis-type) during treatment with immune-checkpoint inhibitor therapies for cancer. Recognition and management of hair-related irAEs are important for pretherapy counseling and interventions that would contribute to maintaining optimal health-related quality of life.